1999
DOI: 10.1006/iilr.2000.0116
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Information-seeking and Communicating Behaviour of Academics

Abstract: A B ST R AC TThis paper discusses the information-seeking behaviour of academics in relation to the productivity of academics in South African Universities, with particular reference to the University of Zululand, through a survey of 105 academics. It was established that the nature of the discipline and the rank of the academic, which normally corresponds with the academic quali¢cation, experience, exposure and research productivity level, largely determine the information-seeking behaviour. Academics mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, previous studies revealed that the personality (Heinstrom 2003), discipline (Ocholla 1999), task performance (Bystrom 2000), work performance (Popoola 2002), users' psychological characteristics (Wilson 2000) and individual characteristics (Allen & Kim 2001) influenced the informationseeking behaviour of users. Before the relevant information is obtained, the searchers must overcome possible obstacles, which are sometimes psychological in nature.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, previous studies revealed that the personality (Heinstrom 2003), discipline (Ocholla 1999), task performance (Bystrom 2000), work performance (Popoola 2002), users' psychological characteristics (Wilson 2000) and individual characteristics (Allen & Kim 2001) influenced the informationseeking behaviour of users. Before the relevant information is obtained, the searchers must overcome possible obstacles, which are sometimes psychological in nature.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Palmer (1996) explored this topic when confirming that scientists bring back specific information from conferences. Ocholla (1999) investigated a similar idea when conducting a study into the information seeking behaviour of academics in South Africa. Participants in this study listed conferences as one of the tools they use to generate new ideas and to disseminate information.…”
Section: Literature Reviewmentioning
confidence: 99%